Variability of Anthoxanthum species in Poland in relation to geographical-historical and environmental conditions: morphological and anatomical variation - Drapikowska, Maria (Biodiversity: Research and Conservation, 2013)
Three Anthoxanthum species are found in Poland: the native A. odoratum L. s. str. and A. alpinum Á. Löve & D. Löve, and the alien A. aristatum Boiss. Major problems within this genus concern: (1) population variation of the native A. odoratum, representing various phases of ecological expansion to anthropogenic habitats; (2) population variation of A. odoratum and A. alpinum along the altitudinal transect; and (3) variation between populations of A. aristatum colonizing new areas and habitats outside its natural range of distribution (chorological expansion). In this study, morphological and anatomical variation of the three Polish Anthoxanthum species was analysed in detail. The variation of A. odoratum and A. aristatum was analysed in respect of environmental differences: habitat types and soil parameters. In the Babia Góra massif, variability distribution along the altitudinal transect was analysed for two vicariants: A. odoratum and A. alpinum. A odoratum in this massif does not cross the upper forest limit (i.e. forest line), and lower montane populations are morphologically very similar to lowland populations. Morphological and anatomical differences were detected between populations of A. alpinum along the altitudinal transect in the Babia Góra massif, with distinct upper montane populations. Moreover, clear morphological differences were found between the two altitudinal vicariants. Lowland populations of A. odoratum are characterized by great morphological variation, only weakly correlated with the type of occupied habitat and the phase of ecological expansion. The detected morphological variation reflects only to a limited extent the environmental variation of occupied habitats, and is not significantly correlated with the phase of chorological expansion. Some soil parameters are significantly correlated with some morphological characters studied in all the Anthoxanthum species. The analysed anatomical features of stems and leaves show continuous variation in the three species.